Assessing Child Abuse Hotline Inquiries in the Wake of COVID-19: Answering the Call - Ortiz, Robin (JAMA Pediatr, 2021)
This cross-sectional study assesses inquiries to a child distress hotline during the COVID-19 pandemic compared with inquiries during the same period the previous year.